Accuracy of Computed Tomography in Small Bowel Obstruction. Issue 6 (June 2013) - Barnett, Rebecca E.; Younga, Jason; Harris, Brady; Keskey, Robert C.; Nisbett, Daryl; Perry, Jonathan; Cheadle, William G.
Small bowel obstruction is a common clinical occurrence, primarily caused by adhesions. The diagnosis is usually made on the clinical findings and the presence of dilated bowel loops on plain abdominal radiograph. Computed tomography (CT) is increasingly used to diagnose the cause and location of the obstruction to aid in the timing of surgical intervention. We used a retrospective chart review to identify patients with a diagnosis of small bowel obstruction between 2009 and 2012. We compared the findings on CT with the findings at operative intervention. Sixty patients had abdominal CT and subsequent surgical intervention. Eighty-three per cent of CTs were correct for small intestine involvement and 80 per cent for colon involvement. The presence of adhesions or perforation was correctly identified in 21 and 50 per cent, respectively. Sixty-four per cent correctly identified a transition point. The presence of a mass was correctly identified in 69 per cent. Twenty per cent of the patients who had ischemic small bowel at surgery were identified on CT. CT has a role in the clinical assessment of patients with small bowel obstruction, identifying with reasonable accuracy the extent of bowel involvement and the presence of masses and transition points. It is less reliable at identifying adhesions, perforations, or ischemic bowel.